THE FREQUENCY OF OWN VIBRATIONS OF THE BYRD OF THE BATAN MECHANISM OF THE LOOM - Dremova Nadezhda Vasilievna (Journal Park Publishing, 2022)
The article considers the natural frequency of the batan mechanism of the loom. Numerical results show that at the initial moment of time, the coefficient significantly affects the displacement. For certain displacement values, the coefficient differs by two and three times. Subsequently, the curves obtained at certain values merge, i.e. coefficient practically does not affect the movement.
Keywords: reed; batan mechanism; natural frequency